Build that wall! Vaccine certificates, passes and passports, the distribution of harms and decolonial global health justice - Arguedas Ramírez, Gabriela (2021)
The implementation of COVID-19 vaccine certificates or passports entails many difficult issues, both technical and ethical. Looking at the ethical issues from a decolonial approach to justice, it is possible to observe that some of them are embedded in long-standing forms of inequality and exclusion, rooted in the legacy of colonialist/imperialist governance. In this paper, my purpose is to explore the potential harms associated with the enforcement of vaccine passports and certificates that do not take into account structural barriers, in the context of global vaccine inequality, from a decolonial and global justice perspective.